Silvicultural Treatments Affect Growth and Foliar Nutrients in a Young Ponderosa Pine Stand - Moore, James A; Fan, Zhaofei; Shaw, Terry M (Forest science, 2023)
Foliar nutrient status, diameter, and height growth were investigated for young ponderosa pine (Pinus ponderosa) stands grown under six fertilizer and herbicide treatments (including control) in southeast Washington to diagnose foliar nutrient status and evaluate the effects of silvicultural treatments on growth rates. Two application methods of fertilizer (one “best guess” multi-nutrient fertilizer blend) and herbicide applications (broadcast or spot) were used in the study. Broadcast herbicide application produced higher tree growth responses than spot application. The two broadcast application methods improved diameter increments by 43.3%, whereas the average response of the three spot application methods during the third growing season was only 14.5%. Height growth response for these same two treatments was much less than the diameter response. Fertilizer application in addition to herbicide did not significantly increase tree growth over herbicide alone. Foliar nutrient response to fertilization based on foliar vector analysis was inconsistent, possibly due to nutrient imbalances resulting from the one multi-nutrient blend used in our experiment. Control of grass completion produced a rapid posttreatment early growth trajectory and suggested that stand establishment was successful in this plantation. Our results should also be useful in naturally regenerated young ponderosa pine forests subject to heavy grass competition. Study Implications: Given the increasing need for reforestation in the western United States, results from our study should provide useful information for forest managers. Stand establishment is a critical phase for ponderosa pine stands. Broadcast herbicide application in a recently established plantation produced a rapid early growth trajectory. In this experiment, reducing severe sod grass competition was the most important factor that increased tree growth. Our results may also apply to naturally regenerated ponderosa pine stands. Fertilization with a multi-nutrient fertilizer blend did not significantly increase tree growth as a separate treatment or when combined with herbicide. Foliar nutrient response to fertilization was inconsistent, possibly due to nutrient imbalances resulting from the multi-nutrient fertilizer blend used in our experiment. Fertilization rate and nutrient composition trials are needed to develop effective fertilization treatments in young ponderosa pine stands. Based on our results, fertilizing without vegetation control is not recommended when there is heavy grass competition. The grasses proliferated following only fertilization to the detriment of the trees. For the conditions in our study, we cannot recommend adding fertilizer in addition to the herbicide as a treatment because fertilization did not significantly increase tree growth over herbicide alone. We feel fertilization rate and nutrient composition trials are needed to develop effective fertilization treatments in young ponderosa pine stands. The establishment of ponderosa pine forests is vital for the future timber they may produce and the ecological benefits they provide. We recommend broadcast herbicide as an effective silvicultural treatment to control competing vegetation (from grasses in our experiment) during the stand establishment of ponderosa pine. As demonstrated in our study, the rapid posttreatment early growth trajectory from vegetation control suggests that stand establishment was successful.